Acute mild gallstone pancreatitis: timing of cholecystectomy - A. A. Mageed, Samir; Helmy, Mena Z.; Redwan, Alaa A. (International Surgery Journal, 2019)
Background: Cholecystectomy is essential to prevent recurrent attacks of mild acute gallstone pancreatitis, but the precise timing of cholecystectomy remains a subject of ongoing debate. The aim of this study is to address the optimal timing of cholecystectomy in patients with mild acute gallstone pancreatitis. Methods: From September 2013 to September 2018, patients with mild acute gallstone pancreatitis were prospectively randomized to either an early laparoscopic cholecystectomy (ELC) versus a delayed laparoscopic cholecystectomy (DLC) group. Recurrent biliary complications, success and failure rate, difficulty of cholecystectomy, operative time, cholecystectomy related complications, length of admission between the two groups were evaluated. Results: A total of 80 patients were randomized to the ELC (41 patients) and to the DLC group (39 patients). There were a statistically significant differences in the total length of hospital stay and recurrent biliary events (4.5±1.1 vs. 7.4±2.6 days, p<0.01 and 4.9% vs. 41%, p<0.001; respectively). There were no differences regarding success and failure rate, difficulty of cholecystectomy, operative time, cholecystectomy related complications, and length of index admission between both groups. Conclusions: In mild gallstone pancreatitis, ELC results in a shorter overall hospital stay with a significant reduction in the recurrent biliary events with no apparent impact on the safety and technical difficulty of the procedure or perioperative complication rate.